Gerotranscendence and Life Satisfaction: Examining Age Differences at the Maha Kumbha Mela - Kalavar, Jyotsna Mirle (Journal of religion, spirituality & aging, 2015)
This study applies scholarship on gerotranscendence and life satisfaction to an under-investigated context, mass pilgrimage sites. It focuses on the Maha Kumbha Mela 2013 Hindu pilgrimage, which took place in Allahabad, India. Drawing on a sample of 200 participants, this study examines the relationship between age, gerotranscendence, and life satisfaction. Using cross-sectional data, the findings show a positive correlation between age and gerotranscendence. Significant age differences in gerotranscendence scores, especially on the cosmic and solitude dimensions, are apparent. However, the relationship between gerotranscendence and life satisfaction was not statistically significant. Implications for the construct of gerotranscendence within Hinduism are discussed.